The Effect of Capital Adequacy Ratio, non Performing Financing, and Financing to Deposit Ratio on Returns for Deposit Results of Sharia Commercial Banks - Rudy Irwansyah; Syahrijal Hidayat (Budapest International Research and Critics University, 2021)
This study aims to see the effect of CAR, NPF, and FDR on the return for the results of mudharabah deposits at Islamic Commercial Banks either simultaneously or partially. The data used in this study are the quarterly financial reports for the period March 2016 to December 2020. The method of analysis used in this study is the method of multiple linear regression analysis using the SPSS 18 program. The F test is used to test the effect of the independent variables, namely CAR, NPF, and FDR on the dependent variable, namely the return on the profit sharing of mudharabah deposits. The t test is performed to test the effect of the CAR, NPF, and FDR variables on the partial return on the return on mudharabah deposits. The significance level used is 5%. The results showed that simultaneously there was an effect between CAR, NPF, and FDR on the Return for Profit Sharing on Mudharabah Time Deposits of 0,802. While partially all 3 independent variables (CAR, NPF, and FDR) also have a significant effect on Return on Time Deposit.